Radial liquid guide structure and biomimetic coagulation protein crown based double mechanism bone defect hemostatic sponge and preparation method thereof

CN122998443APending Publication Date: 2026-10-30SOUTHWEST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510550863.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

(2)对于现有的骨蜡材料,机械封堵骨面渗血,价高且难以清除完全

Benefits of technology

本发明提供一种具有规则径向排列的“微渠”导液结构的负载高凝血活性蛋白冠颗粒的丝素甘油止血海绵,旨在通过物理引流与凝血激活双效协同机制解决颅骨缺损止血难题。当该材料应用于颅骨缺损出血时,拥有径向“微渠”导液结构的海绵从与之贴合的颅骨缺损界面吸收血液。由于其拥有狭小孔隙这一形态结构,毛细现象在此发生。同时,根据Yong-Laplace方程,周围大中心小的梯度孔道结构拥有比竖直孔道更优越的毛细能力,进而有更大的牵引力引导血液快速向海绵中心流动。在这个过程中,由于孔道的不断变窄,直径约为6-9 μm的红细胞受两侧层片阻挡,被截留在海绵圆周的一定区域,并不断堆积,在增大红细胞密度的同时形成血肿。不仅能够固定骨折碎片,防止因骨折碎片移动而损伤局部血管、脑膜及脑组织,进而引发严重并发症;而且有助于促进骨骼的愈合。血液中的水分则在海绵较大的吸水能力与毛细作用下源源不断地被引流至海绵的圆心区域。负载的蛋白冠颗粒接触到血液后被逐一激活,释放出凝血酶,诱发凝血级联反应,实现快速止血。综上所述,本技术将毛细能力诱发的物理引流与凝血酶激发的凝血级联反应相结合,拟构建一种具有快速止血、形成一定量血肿功能的具有规则径向排列“微渠”导液结构的负载高凝血活性蛋白冠颗粒的丝素止血海绵,通过物理、生物双机制协同发挥作用,为临床中的颅骨缺损止血难题提供了一种新的研究思路。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application relates to a kind of preparation method and its use method of hemostatic sponge of high coagulation activity protein crown particle of load with regular radial arrangement liquid guide structure, belong to the technical field of biomedical materials. The skull bleeding is always short of effective response mode due to the problems such as the incompressibility of skull and limited surgical field. The present project is aimed at the characteristics of radial fracture of parietal bone, combined with the knowability of skull defect size in craniotomy, and plans to construct the silk fibroin hemostatic sponge with regular radial arrangement "micro channel" liquid guide structure. The hemostatic sponge that is exactly suitable for the size of bleeding defect, the "micro channel" realizes blood diversion by capillary action, and the gradient size can realize red blood cell interception and enrichment, promote hematoma formation conducive to defect healing;In addition, the high coagulation activity protein crown loaded in "micro channel" releases coagulation factor in the diverted blood, promotes blood clot formation. The present application utilizes the synergistic effect of "physical diversion" and "coagulation activation" mechanism, and is expected to solve the problem of skull defect hemostasis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to hemostatic sponges, specifically to a method for preparing and using a hemostatic sponge with a regularly radially arranged fluid-conducting structure loaded with highly coagulating protein corona particles, belonging to the field of biomedical materials technology. Background Technology

[0002] Hemostasis is a common issue in both clinical and biomedical materials fields. Whether it's uncontrollable continuous bleeding or accidental intraoperative bleeding, failure to achieve rapid and effective hemostasis can increase the risk of complications and surgical failure, even leading to death. In recent years, the field of hemostatic materials has achieved remarkable progress. Among numerous hemostatic materials, hemostatic sponges are widely favored due to their unique porous structure. Further research shows that sponges enhance platelet activation and aggregation at the wound site by providing a porous structure. When vascular tissue is damaged, this structure promotes platelet aggregation and binding to the subendothelial matrix. This interaction generates chemical signals that promote the formation of strong initial hemostatic blockade, thereby improving the overall hemostatic response. Regardless of the type of sponge material, they mostly revolve around two core aspects: ① ensuring a certain level of mechanical strength, and ② maintaining the sponge's unique porous microstructure. The mechanical strength of the sponge directly affects its ability to absorb blood and withstand the effects of blood pressure. Sponges with good mechanical properties can effectively resist blood pressure, thereby improving their hemostatic efficacy; the micromorphological structure of the hemostatic sponge plays a crucial role in its therapeutic effect. This is because it allows them to absorb large amounts of blood while concentrating clotting components, red blood cells, and platelets. This structure promotes platelet adhesion and aggregation upon contact with blood to form a platelet plug, thereby preventing blood from flowing out of the wound. Furthermore, it triggers the release of coagulation-related factors, promoting stable clot formation and effective bleeding control.

[0003] Currently, most traditional surgical hemostasis methods for surgical wounds and trauma first apply absorbable agents to the open wound, then seal the wound with tissue adhesives. However, bone, as mineralized and vascularized connective tissue in the human body, contains a large amount of spongy cancellous bone and a central medullary cavity. Once a fracture occurs, in addition to bone defects, blood continuously seeps from these tiny pores. In cases of severe trauma and critical surgery, damaged or cut bone often suffers from loss of mechanical stability, irregular defect shapes, failed bone regeneration, and bleeding. Currently, traditional hemostatic sponges and other conventional natural or synthetic hemostatic materials (such as hydrogels, bandages, bioadhesives, bioglues, etc.) often struggle to address the unique challenges of bone hemostasis: ① The challenge of complex skeletal anatomy: Bone tissue (especially cancellous bone) is porous and highly vascularized, with scattered bleeding points and abundant blood sinuses. Traditional hemostatic materials struggle to adhere to irregular surfaces, easily leading to leakage and hemostasis failure; ② The challenge of high-pressure blood flow environment: Intraosseous vessels (such as medullary vessels) have high pressure, making conventional physical sealing materials (such as hemostatic powder and bandages) easily dispersed by blood flow or unable to form an effective barrier; ③ The challenge of difficult adhesion at the wetting interface: Blood, tissue fluid, or bone marrow are often present on the bone surface, and the wetting environment significantly reduces the interfacial bonding strength of adhesives (such as fibrin glue and cyanoacrylates). Faced with these challenges, traditional hemostatic materials often exhibit deficiencies such as insufficient mechanical properties, weak interfacial adhesion, poor morphological adaptability, high risk of residue, and complex operation. To date, most hemostatic materials have been applied to major tissues such as skin, liver, and kidneys, with relatively few reports on bone hemostasis. Research on bone hemostatic materials is still in its developmental stage, and there is still a long way to go before commercial application. Developing novel functional materials or modified traditional materials to accelerate bone hemostasis is of urgent significance.

[0004] The skull, one of the strongest bones in the human body, not only maintains the shape and function of the head and face but also plays a crucial role in protecting brain tissue. Skull injuries are generally accompanied by brain damage, meaning the skull, as the first line of defense in the event of traumatic brain injury (TBI), plays a critical initial role in protecting the brain. However, globally, from 1990 to 2016, an estimated 8.4% increase in TBI-related disabilities occurred. In most cases, this increase is associated with increased rates of falls and road-related injuries. Despite primary prevention efforts, this rate is likely to continue to rise due to more frequent use of motor vehicles, unsafe road conditions, and higher alcohol consumption. Furthermore, in some conflict-ridden Middle Eastern countries or countries with high rates of street violence, the incidence of TBI due to war and crime has not decreased significantly in recent years. In other words, skull defects caused by various head injuries and surgeries are highly prevalent in daily life and clinical practice. It is worth noting that the main site of skull defects—the parietal bone—due to its unique dome-shaped morphology, often results in fracture lines radiating outwards from the point of impact when subjected to external force. This is especially true for children's parietal bones, which are more elastic and prone to depressed fractures after trauma. During craniotomy, the removal of a near-round parietal bone is often accompanied by continuous bleeding from complex sources. Due to the parietal bone's location—close to the brain tissue and dura mater—skull control must avoid mechanical compression to prevent further brain damage. Therefore, the surgical space for hemostasis is relatively small; and due to the high surgical field requirements of craniotomy—blood accumulation can obstruct the view. Thus, rapid and efficient hemostasis is crucial to reduce surgical time and the risk of infection and complications. A significant characteristic of the hemostatic response in bone tissue is the formation of a large and prominent blood clot between the fractured bone ends, known as a "hematoma." The formation of hematoma structures helps maintain the integrity of blood vessels within the bone tissue. Most importantly, it can stabilize the final state of a fracture, preventing bone fragments from shifting and damaging key structures such as local blood vessels, meninges, and brain tissue, while simultaneously aiding bone remodeling and promoting inflammatory responses and granulation tissue formation. Furthermore, bone hemostasis is a crucial stage in promoting the ultimate goal of bone healing. The formation of hematoma structures can influence the migration of bone tissue remodeling cells, angiogenesis, and eventual osteogenesis by releasing growth factors (such as bone morphogenetic proteins). Although skull defects are extremely common in reality, there are currently few reports of highly effective hemostatic materials tailored to the characteristics of skull defect bleeding.In summary, cranial defect hemorrhage has the following unique characteristics and requirements: ① The skull has a high proportion of cancellous bone, abundant blood sinuses, and scattered bleeding points with multiple pores; ② It is adjacent to the brain tissue and dura mater, with low subdural vascular pressure but prone to epidural hematoma formation, requiring hemostatic materials to avoid compressing brain tissue or obstructing cerebrospinal fluid circulation; ③ It must simultaneously meet the requirements of rapid hemostasis to expose the intraoperative field of vision and preserve bone regeneration space; ④ The hemostatic material should not affect subsequent bone repair due to excessive mechanical strength or degradation mismatch (e.g., bone cement or titanium mesh implantation is not suitable for cranial defect hemostasis). To address these characteristics, we propose to construct a biosafe silk fibroin hemostatic sponge with a regularly radially arranged "microchannel" fluid-guiding structure. This sponge can rapidly stop bleeding in bone defects of known size (e.g., removing a certain size of skull bone during craniotomy) during surgery and form a hematoma at the defect tip to promote the next stage of bone healing.

[0005] With this goal in mind, the focus of this research is on how to successfully construct a silk fibroin hemostatic sponge with a regularly radially arranged "microchannel" fluid-conducting structure. Directional cryocasting, a simple and universal technique based on ice crystal templates, has attracted widespread attention for constructing various 3D aerogels with hollow and aligned microchannel structures. In a typical cryocasting process, ice crystals nucleate at low temperatures and grow along a temperature gradient, forming a highly oriented parallel ice crystal structure. The ice crystal template is removed by freeze-drying, ultimately yielding a three-dimensional sponge with a parallel-arranged channel structure. Furthermore, the pore structure can be controlled by adjusting the formation and growth process of ice crystals to obtain a highly interconnected pore structure. In recent years, directional cryocasting technology has increasingly focused on the influence of mold shape on the pore structure of materials, and a number of materials using cylindrical molds to prepare radial channels have emerged in various application fields. After studying the preparation methods of these materials, we chose to use a cylindrical copper mold with rapid thermal conductivity to induce ice crystals to grow from the low-temperature source at the circumference of the copper wall towards the center. Since the ice template method often requires the mold to be partially immersed in a liquid cryogenic environment (such as liquid nitrogen or liquid ethanol), ice crystals tend to grow upwards due to the cooling at the bottom, which affects the growth of radial channels. Therefore, we specially formulated PVDF material with excellent thermal insulation properties for the bottom of the mold to reduce this effect.

[0006] Besides efficient physical hemostasis methods, rapid and effective activation of the coagulation cascade is one of the core intrinsic mechanisms of hemostasis. However, thrombin (coagulation factor IIa (FIIa)), a commonly used hemostatic agent in clinical practice, is highly sensitive to environmental temperature, pH, and the properties of the carrier. Commercial thrombin typically needs to be stored at 4°C or below to maintain its enzymatic activity. Studies have shown that thrombin nanocomposites lose significant enzymatic activity over time when stored at 25°C. Therefore, the optimal delivery method for thrombin currently available is cold chain management. However, cold chain delivery consumes a large amount of energy, limits equitable distribution in resource-scarce areas, and shifts the responsibility for safe storage and handling to consumers. In drug delivery, proteins generated in situ on a carrier generally exhibit higher biological activity compared to proteins directly loaded onto a carrier. Therefore, in situ generation of thrombin on a carrier may be a more efficient method to maintain its biological activity. As reported in our previous study, Shi et al. developed a platelet thrombin delivery platform (protein crown CaCO3@CSF / Ca) with a protein corona and carrying high enzymatic activity and excellent room temperature stability. 2+ -P), which can effectively stop bleeding under harsh physiological conditions. In view of this, we loaded this highly coagulable protein crown particles onto the surface of a silk fibroin hemostatic sponge with a regularly radially arranged "microchannel" fluid-guiding structure. This synergistic strategy of physical and biological mechanisms is expected to achieve rapid and efficient hemostasis for skull defect bleeding.

[0007] Regarding the problem of hemostasis in the skull, the currently available commercial solutions and their advantages and disadvantages compared to this invention are as follows: (1) For existing electrocoagulation or ultrasonic bone scalpel techniques, the former generates heat through high-frequency current to denature and close the blood vessel wall proteins, while the latter precisely cuts bone through high-frequency ultrasonic vibration, reducing vascular damage. However, electrocoagulation is accompanied by a high risk of thermal injury, especially in the skull area rich in nerves and brain tissue. Secondly, overuse of this technique can lead to osteonecrosis, which may affect bone healing and increase the risk of postoperative bone flap resorption. At the same time, electrocoagulation is accompanied by smoke interference, requiring real-time auxiliary aspiration, and may obstruct the field of vision during the process. Electrocoagulation and ultrasonic bone scalpel techniques not only require specialized instruments, but their effectiveness also largely depends on the doctor's skill level, resulting in high financial and human resource costs. In particular, ultrasonic bone scalpel techniques may cause bone fracture if not operated properly. This material is simple, readily available, and inexpensive. It can achieve efficient and rapid coagulation simply by placing it in the skull defect area, with low technical difficulty and can save intraoperative time. (2) Existing bone wax materials mechanically seal bone surface bleeding, but are expensive and difficult to remove completely. This makes them prone to acting as foreign bodies, hindering osteoblast activity and increasing the risk of nonunion or infection. Especially in contaminated wounds, they are likely to become carriers for bacterial colonization. In addition, residual bone wax can easily be misdiagnosed as lesions in postoperative images (such as CT scans), affecting the doctor's judgment. This material is inexpensive, has good biocompatibility, and adopts an integrated design. After hemostasis is completed, it can be removed as a whole to expose the surgical field, facilitating subsequent operations, and there is no problem of residue. (3) Existing traditional hemostatic gauze or sponges (such as ordinary sponges or gelatin sponges) that absorb blood and expand to compress and stop bleeding are not suitable for the skull area. This is because excessive packing may compress brain tissue, making it difficult to use, especially in children or in areas with limited space. The sponge developed in this technology has the property of self-shrinking when it comes into contact with liquid. At the same time, due to its high internal porosity, it can still maintain a certain liquid absorption capacity, eliminating the drawbacks of traditional hemostatic sponges; (4) Existing bioadhesive materials (such as fibrin glue, cyanoacrylate) or composite hemostatic agents are used to seal bleeding points by simulating the coagulation cascade reaction or forming a physical barrier. However, fibrin glue contains human / animal-derived components, which are significantly more expensive than traditional materials and may also cause allergic reactions. Secondly, its strength is slightly insufficient, and it usually needs to be combined with other technologies. For example, each Floseal composite biostatic agent, which costs several thousand yuan, is composed of a gelatin matrix and thrombin. It requires a premixing step when used, which takes up valuable rescue time in emergency situations. This technology uses readily available silk fibroin and glycerin as raw materials, and prepares protein crown particles loaded with in-situ thrombin-generating particles according to previous technology. Upon contact with blood, it triggers the coagulation cascade reaction, achieving efficient coagulation while maintaining a low production cost. (5) Existing absorbable materials (such as oxidized regenerated cellulose Surgicel, microfibrillated collagen Avitene, and chitosan-based materials) have the following disadvantages: the acidic environment created by oxidized regenerated cellulose may damage nerves and cannot be used on infected wounds; microfibrillated collagen particles may migrate into the cerebrospinal fluid, thereby causing aseptic meningitis; clinical data on chitosan-based materials are limited, and their adhesiveness often decreases in a moist environment rich in blood. In contrast, the hemostatic sponge used in this technology is disposable and easy to operate. Furthermore, the protein crown particles are blended with an equal proportion of protonated tranexamic acid, which will react upon initial contact with blood, dissolving the particles while maintaining a neutral or slightly alkaline environment; Summary of the Invention

[0008] To address the problems in the prior art, according to a first aspect of the present invention, the present invention provides a method for preparing a hemostatic sponge with a regularly radially arranged liquid-guiding structure loaded with highly coagulating protein crown particles. The hemostatic sponge prepared by this method has four prominent features: First, we add the cross-linking agent ethylene glycol diglycidyl ether to the traditional silk fibroin glycerol system, which strengthens the mechanical strength of the sponge while solving the problem of easy dissolution of the silk fibroin glycerol system upon contact with water; Second, the sponge has a unique dense radially arranged lamellar structure, which can physically retain red blood cells with a diameter of about 6-9 μm during the absorption of blood, while continuously guiding small molecule components in the blood into the interior of the material, achieving sieving and physically increasing the red blood cell density; Third, the protein crown particles loaded with in-situ thrombin-generating particles trigger a coagulation cascade reaction upon contact with water. The dual hemostasis mechanisms of physical and biological processes work together to achieve efficient and rapid coagulation; fourth, the protein crown particles and protonated tranexamic acid particles are mixed and loaded in equal proportions, and the CaCO3 shell of the protein crown reacts with acid and dissolves instantly upon contact with water, so that there are no powdery particles left on the wound surface, while maintaining a neutral or slightly alkaline environment.

[0009] Specifically, to achieve the above objectives, the technical solution of the present invention is as follows: (1) Preparation of a silk fibroin hemostatic sponge with a regularly radially arranged liquid-conducting structure: First, according to reported literature, a ternary solution was used to dissolve the silk fibroin. First, the ends of the silkworm cocoons were cut to remove the pupae, and the surrounding silk fibers were manually removed to obtain pretreated cocoons. Next, the cocoons were degummed. 20 g of silkworm cocoons were immersed in a solution with a concentration of 0.02 mol·L⁻¹. -1The degummed silk fibroin fibers were boiled in a Na2CO3 solution (2 L) at 100℃ for 60 min. Then, the fibers were washed several times with distilled water until impurities and Na2CO3 were removed and the fibers were no longer slippery. They were then dried in a 60℃ oven for 12 h. Next, the degummed silk fibers were dissolved in a ternary solution (CaCl2:C2H5OH:H2O=1:2:8 mol) at 80℃ for 2 h, with a bath ratio of 1:10. The mixed solution was poured into a 3500 molecular weight dialysis bag and dialyzed for three days, changing the water three times a day (morning, noon, and evening). Finally, the dialyzed pure silk fibroin solution was frozen and then freeze-dried for 2-3 days to obtain dried silk fibroin for later use. The second step involved preparing a silk fibroin-glycerol mixed solution. The silk fibroin was weighed and redissolved to prepare a 3% (w / v) silk fibroin solution. Different masses of glycerol were added to prepare mixed solutions ranging from 0% to 15% (w / w) (5% concentration showed the strongest water absorption capacity). According to reported literature, 0–200 μL of the cross-linking agent ethylene glycol diglycidyl ether (EGDE) was added to every 10 mL of an 11% (w / v) silk fibroin solution, with 100 μL being the preferred amount due to its strongest water absorption capacity. The required volume of EGDE to be added after proportional scaling was calculated based on the silk fibroin concentration ratio used in the literature and this technique. After mixing at room temperature, 7 μL of tetramethylethylenediamine was added to every 10 mL of the mixed solution to catalyze the reaction, which was carried out for 10 min. The third step involved radial freezing using directional cryogenic casting technology. A specially made cylindrical mold was prepared, and a cylindrical tube was fabricated using rapidly conductive copper (in the embodiments given in this technique, a cylindrical tube with an inner diameter of 3 cm, an outer diameter of 4.6 cm, and a height of 4 cm was fabricated). The bottom was insulated with a 1 cm thick layer of polyvinylidene fluoride (PVDF). Pour liquid nitrogen into a foam box until the liquid level is slightly higher than 1 cm. Pour the mixed solution into the mold and immediately place the mold into the liquid nitrogen. Wait for the ice crystals to grow completely from the wall of the tube towards the center. Place the mold in a -80°C freezer to fix it for at least 15 minutes. Fourth, freeze-dry the mold in a freeze dryer for 2-3 days. After demolding, you will obtain a silk fibroin hemostatic sponge with a regularly radially arranged liquid-conducting structure.

[0010] (2) Protein crown with high coagulation activity (CaCO3@CSF / Ca 2+-P) Particle Preparation: Ternary solution-dissolved silk fibroin was prepared using the same steps as described above. First, according to reported literature, equal volumes of 0.33 M CaCl2 and 0.33 M Na2CO3 were mixed for 30 s, allowed to stand for 10 min, washed three times with deionized water, and vacuum dried to synthesize the CaCO3 framework. Second, following our previous technique, a multilayer chitosan (CS) / silk fibroin (SF) film (CSF) was deposited on the surface of the CaCO3 particles. Specifically, a 0.5 mg·mL⁻¹ CSF was prepared beforehand. -1 CS solution (0.1 M NaCl, pH 5.5) and 1 mg·mL -1 SF solution (0.1 M NaCl, pH 5.5). 500 μL of acetic acid can be added before dissolving CS to promote dissolution. Acidity and alkalinity are adjusted using dilute hydrochloric acid and concentrated NaOH solution. CaCO3 (2 wt%) is immersed in CS solution for 15 min, centrifuged at 2000 rpm for 1 min, washed three times with NaCl solution (0.1 M, pH 5.5), then immersed in SF solution for 15 min, centrifuged at 2000 rpm for 1 min, and washed three times with NaCl solution (0.1 M, pH 5.5). This process is repeated 1-5 times, preferably 4 times for the shortest clotting time. The centrifugation speed is adjusted to 1000 rpm in the last two steps. Finally, it is washed three times with deionized water and lyophilized to obtain the platelet-like precursor CaCO3@CSF. The third step involves loading calcium ions (Ca... 2+ CaCO3@CSF particles (50 mg) were incubated in CaCl2 solution (0.6 M) for 3 h (in a 37℃ constant temperature shaker), washed twice with deionized water, frozen, and then freeze-dried to obtain platelet-like CaCO3@CSF / Ca 2+ Step four: In-situ thrombin generation. Platelet-rich plasma (PRP) was obtained by centrifuging pig blood at 3000 rpm for 10 min. The PRP was stored at -80°C until use. Then, CaCO3@CSF / Ca... 2+ (0.1 g) was mixed in 400 μL (50% (v / v)) of anemic platelet-rich plasma diluted with 0.9% NaCl saline for 3–5 min until an insoluble flocculent precipitate formed. The resulting precipitate was lyophilized to obtain the thrombin delivery platform—protein crown CaCO3@CSF / Ca 2+ -P particles.

[0011] (3) Preparation of protonated tranexamic acid: Following our previous technique, a 0.5 M aqueous solution of tranexamic acid was prepared, and the pH was adjusted to 4.0 with hydrochloric acid. After freeze-drying, powdered protonated tranexamic acid (TXA-NH3) was obtained. + ).

[0012] (4) Preparation of a hemostatic sponge with a regularly radially arranged fluid-conducting structure and loaded with high coagulation activity protein corona particles: First, CaCO3@CSF / Ca 2+ -P particles and TXA-NH3 + The powders were physically mixed at a molar ratio of 1:1. A radial sponge was placed in a container containing the mixed powder and gently shaken for 5 minutes. The mixed particles containing a high coagulation activity protein crown were loaded onto the sponge surface by electrostatic adsorption.

[0013] According to a second aspect of the present invention, the present invention provides a method of using the hemostatic sponge having a regularly radially arranged fluid-guiding structure loaded with highly coagulable protein coagulant particles.

[0014] The method for using the aforementioned hemostatic sponge with a regularly radially arranged fluid-guiding structure loaded with highly coagulable protein crown particles is characterized by: pre-cutting the hemostatic sponge according to the common defect sizes in craniotomy to achieve a diameter suitable for defects ranging from 3 to 80 mm. Large-sized sponges are made using large-sized molds, while small-sized sponges can be made using small molds or by cutting. Specifically, before the fourth stage of the preparation process—the loading of protein crown particles—the demolded radial sponge is cut into thin sheets with a thickness of 1.5 cm to adapt to the thickness of the human skull, preventing excessive thickness from compressing cranial nerves or brain tissue. The radial sponge sheets are immersed one by one in liquid nitrogen for 3 seconds, removed for 9 seconds, and immediately cut using a circular cutter of different diameters to obtain radial sponges adaptable to different defect sizes. After loading with mixed particles containing highly coagulable protein crowns, the sponge can be stored for later use. During surgery, when bleeding occurs at the burr site, the hemostatic sponge can be placed at the bleeding site. The sponge rapidly absorbs blood and fluid while contracting, and the thrombin particles trigger a coagulation cascade reaction, achieving rapid hemostasis. The mixed particles react with each other and self-dissolve, preventing particle residue or migration to other sites. After hemostasis is achieved, the sponge is removed to proceed to the next step.

[0015] Beneficial effects: This invention provides a silk fibroin glycerol hemostatic sponge with a regularly radially arranged "microchannel" fluid-guiding structure loaded with highly coagulating protein crown particles, aiming to solve the problem of hemostasis in skull defects through a dual-effect synergistic mechanism of physical drainage and coagulation activation. When this material is applied to skull defect bleeding, the sponge with the radial "microchannel" fluid-guiding structure absorbs blood from the interface of the skull defect it adheres to. Due to its narrow pore structure, capillary action occurs. Simultaneously, according to the Yong-Laplace equation, the gradient pore structure with a larger periphery and a smaller center has superior capillary capacity than vertical pores, thus providing greater traction to guide blood to flow rapidly towards the center of the sponge. During this process, as the pores continuously narrow, red blood cells with a diameter of approximately 6-9 μm are blocked by the lateral lamellar structures, trapped in a certain area around the circumference of the sponge, and continuously accumulate, increasing red blood cell density and forming a hematoma. This not only fixes fracture fragments, preventing damage to local blood vessels, meninges, and brain tissue due to fragment movement and thus avoiding serious complications, but also helps promote bone healing. Water from the blood is continuously drained to the central area of ​​the sponge due to its high absorbency and capillary action. Upon contact with the blood, the loaded protein corona particles are activated one by one, releasing thrombin and inducing a coagulation cascade reaction, achieving rapid hemostasis. In summary, this technology combines capillary-induced physical drainage with thrombin-induced coagulation cascade reaction to construct a silk fibroin hemostatic sponge with a regularly radially arranged "microchannel" drainage structure loaded with highly coagulable protein corona particles. This sponge, through the synergistic effect of both physical and biological mechanisms, provides a new research approach for addressing the challenge of hemostasis in clinical skull defects. Attached Figure Description

[0016] Figure 1 This is a schematic diagram of the preparation of a hemostatic sponge with a regularly radially arranged fluid-conducting structure and a high coagulation activity protein corona particles, and a schematic diagram of the hemostatic principle.

[0017] Figure 2 This is a diagram illustrating the optimal material ratio and chemical structure characterization. (A) shows the water absorption ratio of sponges with different amounts of crosslinking agent; (B) shows the water absorption ratio and shrinkage ratio with different amounts of glycerol; (C) shows the compressive stress-strain curves of SF, SF+G, and SF+G+E sponges; (D) shows the ATR-FTIR spectra of SF, SF+G, SF+G+E sponges and EGDE; (E) shows the proportions of α-helical and β-sheet structures in SF, SF+G, and SF+G+E sponges after peak fitting of the infrared spectra; and (F) shows the thrombin activity of the pure sponge group without P, ​​the pure protein crown group P, and the sponge group with protein crown loaded with P.

[0018] Figure 3These are material physical structure characterization diagrams. Among them, (A) is a top-view SEM image of the radial sponge; (B) is a SEM image of the randomly porous sponge; (C) is the interlaminar spacing at different locations of the radial sponge from the center; (D) is a small-field SEM image of the radial sponge at different locations from the center; (E) is an inverted fluorescence microscope image of the protein crown particles after encapsulation; (F) is a CSF membrane microscope image after the encapsulated protein crown has been etched; and (G) is a SEM image of the radial sponge loaded with protein crowns.

[0019] Figure 4 This is a radial sponge sieving and capillary capacity evaluation diagram. Among them, (A) is the dynamic blood contact angle of the radial sponge edge, center and random pore size sponge; (B) is the SEM image of the radial sponge after blood absorption, the center (b) and edge (a) of the cross section adsorbing red blood cells; (C) is the image of the radial sponge edge, center of the radial sponge and the random pore size group absorbing liquid after liquid is added.

[0020] Figure 5 This is a graph evaluating the in vitro hemostatic performance of the material. Among them, (A) is a physical image of the hemostatic time of the blank, Without P, ​​P, and With P groups; (B) is a graph of the hemostatic time of the Without P, ​​P, and With P groups; (C) is a SEM image of the adhesion of red blood cells and platelets in the Without P, ​​P, and With P groups; (D) is a physical image of the supernatant in the Without P, ​​P, and With P groups in the BCI test; and (E) is a grouped statistical graph showing the change of the coagulation index BCI with hemostatic time.

[0021] Figure 6 This is a chart evaluating the biosafety and in vivo hemostatic performance of the materials. (A) shows immunofluorescence staining of live / dead cells in the Without P, ​​P, and With P groups at 24 h and 48 h (green: live cells; red: dead cells); (B) shows cell viability of the Without P, ​​P, and With P groups after co-culturing with cell extracts for 24 h and 48 h using the CCK8 assay (untreated cells served as a blank control); (C) is a screenshot from a video showing the application of radial sponges at the edge and center sites for hemostasis in a rat liver hemostasis model; (D) is a screenshot from a video showing the application of Random sponge with random pore size, Radial sponge, and Radial@P sponge loaded with a protein crown in a rat skull defect hemostasis model. Detailed Implementation

[0022] The present invention will now be described in detail through specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-described invention.

[0023] (I) Synthesis of silk fibroin hemostatic sponge with regularly radially arranged "microchannel" fluid-guiding structure loaded with protein crown Example

[0024] (1) Preparation of silk fibroin hemostatic sponge with a regularly radially arranged "microchannel" fluid-guiding structure The first step, according to reported literature, was to obtain a silk fibroin solution using a ternary solution. First, the ends of the silkworm cocoons were cut to remove the pupae, and the surrounding fibrous material was manually removed to obtain pre-treated cocoons. Next, the cocoons were degummed. 20 g of silkworm cocoons were immersed in a solution with a concentration of 0.02 mol·L⁻¹. -1The degummed silk fibroin fibers were boiled in a Na2CO3 solution (2 L) at 100℃ for 60 min. Then, the fibers were washed several times with distilled water until impurities and Na2CO3 were removed, and dried in a 60℃ oven for 12 h. Next, the degummed silk fibers were dissolved in a ternary solution (CaCl2:C2H5OH:H2O=1:2:8mol) at 80℃ for 2 h, with a bath ratio of 1:10. The mixed solution was poured into a 3500 molecular weight dialysis bag and dialyzed for three days, changing the water three times a day (morning, noon, and evening). Finally, the dialyzed pure silk fibroin solution was frozen and then freeze-dried for 2-3 days to obtain dried silk fibroin for later use. The second step involves preparing a silk fibroin-glycerol mixed solution. The silk fibroin was weighed and redissolved to prepare a 3% (w / v) silk fibroin solution. Different masses of glycerol were added to prepare mixed solutions of 0%, 5%, and 15% (w / w) for single-factor experiments to investigate the glycerol content with the optimal water absorption ratio. According to reported literature, 0, 50, 100, and 200 μL of the cross-linking agent EGDE were added to every 10 mL of an 11% (w / v) silk fibroin solution for single-factor experiments to investigate the cross-linking agent content with the optimal water absorption ratio. The required volume of EGDE to be added after proportional scaling was calculated based on the concentration ratio of the silk fibroin solution used in the literature and this technique. The mixture was mixed at room temperature, and 7 μL of tetramethylethylenediamine was added to every 10 mL of the mixed solution to catalyze the reaction, which was carried out for 10 min. In the third step, radial freezing was performed using directional cryogenic casting technology. A specially made cylindrical mold was prepared, and a circular tube with an inner diameter of 3 cm, an outer diameter of 4.6 cm, and a height of 4 cm was made using rapidly heat-conducting copper. The bottom was insulated with 1 cm thick polyvinylidene fluoride (PVDF). Liquid nitrogen was poured into a foam box until the liquid level was slightly above 1 cm. The mixed solution was poured into a mold, and the mold was immediately placed in the liquid nitrogen. Ice crystals were allowed to grow completely from the tube wall towards the center. The mold was then placed in a -80°C freezer for at least 15 minutes to fix the solution. In the fourth step, the mold was freeze-dried for 2-3 days. After demolding, a silk fibroin hemostatic sponge with a regularly radially arranged liquid-conducting structure was obtained. The control group, with sponges of random pore size, was directly frozen at -80°C for 1 hour after being poured into the mold to allow for random anisotropic ice crystal growth. The final sample was also freeze-dried and demolded.

[0025] (2) Protein crown with high coagulation activity (CaCO3@CSF / Ca 2+ -P) Particle Preparation The ternary solution-dissolved silk fibroin was prepared using the same steps as described above. First, according to reported literature, equal volumes of 0.33 M CaCl2 and 0.33 M Na2CO3 were mixed for 30 s, the solution was allowed to stand for 10 min, washed three times with deionized water, and vacuum dried to synthesize the CaCO3 framework. Second, following our previous technique, a multilayer CS / SF film was deposited on the surface of the CaCO3 particles. Specifically, 0.5 mg·mL⁻¹ of CS / SF film was prepared beforehand. -1 CS solution (0.1 M NaCl, pH 5.5) and 1 mg·mL -1 SF solution (0.1 M NaCl, pH 5.5). 500 μL of acetic acid can be added before dissolving CS to promote dissolution. Acidity and alkalinity are adjusted using dilute hydrochloric acid and concentrated NaOH solution. CaCO3 (2 wt%) is immersed in CS solution for 15 min, centrifuged at 2000 rpm for 1 min, washed three times with NaCl solution (0.1 M, pH 5.5), then immersed in SF solution for 15 min, centrifuged at 2000 rpm for 1 min, and washed three times with NaCl solution (0.1 M, pH 5.5). This process is repeated four times. In the last two steps, the centrifugation speed is adjusted to 1000 rpm. Finally, it is washed three times with deionized water and lyophilized to obtain the platelet-like precursor CaCO3@CSF. The third step involves loading Ca... 2+ CaCO3@CSF particles (50 mg) were incubated in CaCl2 solution (0.6 M) for 3 h (in a 37℃ constant temperature shaker), washed twice with deionized water, frozen, and then freeze-dried to obtain platelet-like CaCO3@CSF / Ca 2+ Step four: In-situ thrombin generation. Pig blood was centrifuged at 3000 rpm for 10 min to obtain anemic platelet plasma. The anemic platelet plasma was stored at -80℃ until use. Then, CaCO3@CSF / Ca... 2+ (0.1 g) was mixed with 400 μL (50% (v / v)) of anemic platelet plasma diluted with 0.9% NaCl saline for 3–5 min until an insoluble flocculent precipitate was formed. The resulting precipitate was frozen and then lyophilized to obtain the protein crown CaCO3@CSF / Ca 2+ -P particles.

[0026] (3) Preparation of silk fibroin hemostatic sponge with regularly radially arranged "microchannel" fluid-guiding structure loaded with high coagulation activity protein crown Following our previous technique, a 0.5 M tranexamic acid aqueous solution was prepared, and the pH was adjusted to 4.0 with hydrochloric acid. After freeze-drying, protonated tranexamic acid (TXA-NH3) powder was obtained. +). TXA-NH3 + Powder with CaCO3@CSF / Ca 2+ -P particles were physically mixed at a molar ratio of 1:1. In animal experiments, an 8 mm diameter circular defect was artificially drilled into the skull of SD rats. Two pieces of sponge were cut into 2 mm thick slices to fit the thickness of the rat skull. The radial sponge slices were immersed in liquid nitrogen for 3 seconds, removed for 9 seconds, and immediately cut using an 8 mm diameter circular cutter to obtain radial sponges that fit the defect size. The cut 8 mm radial sponge slices and ordinary radial sponges were placed in a container containing the mixed powder and gently shaken for 5 minutes. The mixed particles containing a high coagulation activity protein crown were electrostatically adsorbed onto the sponge surface, resulting in the With P mixture. The control group did not undergo the particle loading process and was designated Without P.

[0027] (II) Performance testing of the silk fibroin hemostatic sponge with a regularly radially arranged "microchannel" fluid-guiding structure loaded with protein crown prepared in Example 1.

[0028] (1) Protein crown CaCO3@CSF / Ca 2+ The successful preparation and successful loading of -P were verified. The success of CSF deposition is a crucial factor in the successful preparation of in-situ thrombin protein corona. Specifically, in artificial platelets, Ca... 2+ The bridging effect is crucial for the in situ prothrombin-catalyzed thrombin formation. This is because SF and Ca... 2+ The strong interaction between them makes SF suitable for creating SF / Ca 2+ Interface to mimic the natural phosphatidylserine (PS) / Ca on platelets 2+ Structure. However, the negative zeta potential of CaCO3 repels soluble SF polymers, therefore it is necessary to alter the surface charge of CaCO3 to make it positively charged, allowing electrostatic adsorption of negatively charged SF / CaCO3 polymers. 2+ Polymer complex. Therefore, we coated the CaCO3 surface with chitosan, the only naturally occurring cationic polymer among soluble polymers. It is this modification that creates SF / Ca... 2+ This provides complex adsorption sites. Therefore, before freezing the CaCO3@CSF particles, we observed the deposition of the CSF film using an inverted fluorescence microscope (IX73, Olympus, Japan). First, a drop of the particle suspension was placed on a glass slide to observe its overall physical morphology. Then, a 0.5 M tranexamic acid aqueous solution was added to the edge of the droplet, and the etching of the particles and the integrity and fullness of the pure CSF film remaining after the reaction with CaCO3 were observed under the microscope. Figure 3As shown in Figure E, the particles are perfectly spherical with a diameter of 4–8 μm. After etching, the CSF film remains intact and has a certain thickness, indicating that a CSF film has been successfully deposited on the CaCO3 surface, which can support Ca. 2+ ( Figure 3 F).

[0029] The successful loading of the protein crown was initially verified by scanning electron microscopy (SEM, SU8010, Hitachi). Thrombin activity was further verified by measuring thrombin activity using thrombin chromogenic substrates (S-2238, S27564, Yuanye Bio, China). Initially, CaCO3@CSF / Ca... 2+ (0.1 g) was mixed in 400 μL (50% (v / v)) of anemic platelet-rich plasma diluted with 0.9% NaCl saline for 3–5 min until an insoluble flocculent precipitate formed. Next, the collected particles (15 mg) were mixed with 100 μL of phosphate-buffered saline (PBS) and 100 μL of S-2238 solution (0.4 mg / mL). -1 Incubate together. After 2 min of incubation, immediately add 50 μL of acetic acid solution (50% (v / v)) to terminate the reaction. Centrifuge at 5000 rpm for 3 min and collect the supernatant. Measure the absorbance at 405 nm, repeating the test three times. Determine thrombin activity using a thrombin calibration curve. Next, test the thrombin activity of the pure radial sponge group and the radial sponge group loaded with protein crowns using the same method, repeating each group three times.

[0030] We can Figure 3 In G, protein corona particles with a diameter of approximately 10 μm were observed to be stably present between the sponge strata, indicating that the protein corona had been loaded onto the sponge surface through electrostatic adsorption. Figure 2 As shown in Figure F, the average thrombin activity of the pure protein corona reached 1.16 U / mL, far exceeding the generally accepted positive threshold of 0.2 U / mL, which is sufficient to prove the successful preparation of the in situ generated thrombin protein corona. Furthermore, compared to the 0.19 U / mL negative value of the control radial sponge, both the protein corona and the radial sponge group loaded with protein corona showed outstanding thrombin activity (1.16 U / mL and 0.92 U / mL, respectively), which strongly demonstrates the successful loading of a highly coagulable protein corona onto the hemostatic sponge.

[0031] (2) Exploration of optimal ratio and determination of chemical structure Single-factor experiments were used to test the water absorption ratio of the dried samples. Specifically, samples (1.5×1.5×1.2 cm) containing 5% (w / w) glycerol and 0, 50, 100, and 200 μL / 10 mL of 11% (w / v) silk fibroin solution were prepared. The initial weight W was measured, and the samples were immersed in deionized water. After saturation, excess water was removed from the area around the sponge, and the weight was recorded as W'. The water absorption capacity of the sponge after adding different cross-linking agents was calculated: Water absorption ratio (Multiple) = W' / W. The same group of samples was repeated three times, and the average value was calculated. Figure 2 Data A indicates that the material group with 100 μL / 10 mL of 11% (w / v) SF solution (hereinafter referred to as 100 μL) exhibits the best water absorption capacity, capable of absorbing more than 12 times its own mass of liquid. The water absorption capacity of samples (1.5 × 1.5 × 1.2 cm) with 100 μL of EGDE and glycerol contents of 0%, 5%, and 15% (w / w) were tested using the same method. Simultaneously, the thickness H (cm) of the structured sponge after water saturation was measured, and the sponge's shrinkage rate was calculated as (1.2 - H) / 1.2h × 100%. Figure 2 Data from B indicates that the sponge with 5% (w / w) glycerol exhibits the best absorbency, capable of absorbing more than 16 times its own weight in liquid. While self-shrinking properties are also desirable, greater shrinkage clearly means sacrificing the amount of liquid the sponge can retain. Our goal is simply to prevent the sponge from swelling at the site of skull hemorrhage, potentially compressing nerves or brain tissue; therefore, a sponge with a certain degree of shrinkage (not necessarily high) and the highest possible absorbency is required. Consequently, we ultimately determined the optimal component concentrations to be 5% (w / w) glycerol and 100 μL of EGDE.

[0032] Fourier transform attenuated total reflectance infrared spectroscopy (ATR-FTIR) was used in the range of 4000–400 cm⁻¹. -1 The functional groups of EGDE, SF, SF+G, and SF+G+E were determined by scanning within a specific wavelength range. This was used to demonstrate the crosslinking induced by the crosslinking agent. The compressive mechanical properties of pure silk fibroin sponge SF, silk fibroin sponge with 5% (w / w) glycerol SF+G, and silk fibroin sponge with 5% (w / w) glycerol and 100 μL crosslinking agent SF+G+E were tested using an Autograph AGS-X universal testing machine (Shimadzu, Kyoto, Japan) to verify the crosslinking-enhanced mechanical strength. Rectangular specimens (1.5 × 1.5 × 1.2 cm) were tested at 10 mm·min⁻¹. -1 The compression rate was tested, and the test was stopped when the strain reached 80%.

[0033] first, Figure 2 In the ATR infrared spectrum of D, at 887 cm⁻¹ -1 A symmetric stretching vibration peak of the COC group appeared at 1269 cm⁻¹. -1 An asymmetric stretching vibration peak of the COC group appeared at the peak. This is due to the ring-opening reaction of the epoxy group of EGDE, which crosslinks with the abundant hydroxyl groups in the system to form COC chemical bonds. This confirms the successful crosslinking of EGDE. Next, we performed peak finding and peak fitting for the α-helical and β-sheet structures in the amide I band. The amide I band was chosen because it is mainly caused by the stretching vibration of C=O, which is extremely sensitive to small changes in the secondary structure of proteins. The absorption peak positions of different secondary structures are significantly different, making it suitable for peak fitting and quantitative calculation. In addition, the peak shape of the amide I band is narrow and the resolution is high. After deconvolution or second derivative spectrum processing, the sub-peaks can be more clearly distinguished. Based on this, we calculated the peaks in the 1650–1660 cm⁻¹ range. -1 The peak area of ​​the characteristic α-helical structure within the range of 1620–1640 cm⁻¹ -1 The peak area ratio of the characteristic peaks of the β-fold structure within the range. Figure 2 C and Figure 2 The combined data from E show that the addition of glycerol and cross-linking agents allows the sponge to withstand greater stress under the same strain, resulting in a higher compressive modulus. This change in mechanical properties is mainly due to the formation of hydrogen bonds and COC chemical bonds through the addition of glycerol and EGDE, thereby enhancing the intermolecular bonding strength. Although the reduction of the β-sheet structure in the secondary structure of silk fibroin is detrimental to the increase in mechanical strength, the strengthening effect produced by the addition of chemical bonds far outweighs the weakening effect of the secondary structure. The increased mechanical strength of the sponge will help it effectively resist blood pressure, thus improving its hemostatic efficacy.

[0034] (3) Radial sponge screening performance evaluation The formation of radially radiating lamellar structures in the microstructure was confirmed using scanning electron microscopy (SEM, SU8010, Hitachi).

[0035] Immerse the radial sponge in anticoagulated whole blood until it is completely absorbed. Carefully remove the sponge and fix it in 2.5% (v / v) glutaraldehyde solution overnight. Wash it 2-3 times with PBS buffer for 1-2 minutes each time to remove unfixed red blood cells, fixative, and impurities. Prepare 70%, 80%, 90%, and 100% ethanol solutions. Immerse the material in ethanol solutions of varying concentrations from low to high for 10 minutes each to ensure that the intracellular water is fully replaced by the ethanol. Place the material in a ventilated area to dry and then perform a longitudinal section. Observe the red blood cell density at the edge and inside of the longitudinal section under a scanning electron microscope.

[0036] Compared to Figure 3 The random pore orientation of B indicates that the sponge prepared by directional cryogenic casting exhibits a distinct radial lamellar structure. Figure 3 A). Under magnification in the top view, the layers are arranged in parallel within a small scale ( Figure 3 D), forming microchannels capable of capillary action. The lamellar spacing varies at different locations from the center, generally increasing from the center to the circumference. That is, the microchannels are essentially trapezoidal in shape, narrow at the center and wide at the periphery, providing greater capillary force than channels with a single spacing. Furthermore, sufficiently small lamellar spacing is also desirable. Measurements of lamellar spacing using ImageJ software show that radial pores have lamellar spacing of less than 6–9 μm (…). Figure 3 (C) This physically blocks and separates red blood cells from small water molecules, increasing red blood cell density to promote clotting. It can be seen that the red blood cell density on the outer side is much greater than on the inner side, while the red blood cells on the inner side also have a relatively smaller average diameter.

[0037] (4) Construction of radial sponge physical model and investigation of capillary capacity Based on the actual structures of random and radial sponges, cylindrical random channels and cylindrical radial channels were modeled using SolidWorks software. Computational fluid dynamics analysis was performed in COMSOL, with the fluid density set to 1060 kg / m³. 3 The dynamic viscosity was set to 0.0035 Pa·s (simulating blood properties), the inlet flow velocity was set to 0.4 m / s (peak aortic blood flow velocity), and the outlet static pressure was zero. The permeability of the sponge was evaluated along the direction of maximum flow.

[0038] Radial sponges and randomly pore-sized (random group) sponges were cut into 2 mm thin slices. Each radial slice was further cut into two semi-circular slices. Using tweezers, the arc portion (where the liquid moves from the center to the circumference under capillary action, designated the center group) and the diameter portion (where the liquid moves from the circumference to the center under capillary action, designated the edge group) were held separately and fixed in a vertical plane. Using a dropper, 1 mL of methylene blue-dyed deionized water was added to the bottom of the sponge. A mobile phone camera was used to record the capillary behavior and water absorption rate of the colored liquid in sponges with different pore sizes. A contact angle meter (KRUSS, DSA100) was used to monitor the dynamic blood contact angle of the sponges with liquid added from the circumference (edge ​​group), the center group, and the random pore-sized sponge group. A camera recorded the change in contact angle of 8 μL of anticoagulated pig blood upon contact with a sponge over absorption time. Contact angle measurements were performed frame-by-frame to obtain dynamic contact angle curves. Multiple curves were obtained by repeating the process three times for each sample and then overlaid on a single image for unified analysis. Based on the interlaminar spacing and tilt angle data obtained from previous radial sponge cross-sectional SEM images and data from water contact angle tests, the Yong-Laplace equation was used to calculate the difference in capillary pressure compared to ordinary vertical channels. (α: water surface tension; θ: water-channel wall contact) First, regardless of the pore size, the initial contact angle of the sponge is less than 90°, indicating that the material is hemotropic. Furthermore, it is easy to see that radial pores, compared to random pores, provide a relatively unobstructed space, allowing the liquid to flow with less resistance. This can be seen in the dynamic contact angle curve of the random pore size group (…). Figure 4 (A) To the right of the red dashed line, the absorption rate of the material in the random pore group is significantly slowed down. Compared to the slow, small-scale diffusion of the liquid in the random pore group, the edge and center groups, with their interconnected channels, exhibit more pronounced upward diffusion. Figure 4 C). In Figure 4 In the dark background areas of region A, regardless of whether blood flows from the circumference to the center or from the center to the circumference, they exhibit shorter absorption times than those with random pores. The edge group, in particular, enhanced by positive capillary action, demonstrates a deeper ascent distance and the highest water absorption rate. Figure 4 C).

[0039] (5) Investigation on the in vitro hemostatic performance of hemostatic sponge The hemostatic activity of radial sponge Without P, ​​pure protein crown P, and radial hemostatic sponge With P loaded with a high coagulation activity protein crown was evaluated using the coagulation index (BCI) test and whole blood coagulation assay. For the BCI test, 100 μL of fresh anticoagulated porcine blood was dropped onto 20 mg of material and 10 μL of CaCl2 (0.2 M), and incubated at 37 °C for 1, 3, 5, 7, 9, and 11 min, respectively. Then, 1 mL of deionized water was added to lyse uncoagulated red blood cells, and the mixture was incubated at 37 °C for another 15 min. The supernatant (100 μL) of each sample was measured using a UV spectrophotometer (U-3900, Tianmei Scientific Instruments Co., Ltd.).

[0040] Among them OD control It is the absorbance of the untreated blank group, OD sample This is the absorbance of the supernatant in the sample. The BCI can be calculated by the ratio of the two. For the coagulation test, 0.05 g of different samples were added to 2 mL of fresh anticoagulated porcine blood and 80 μL of CaCl2 (0.2 M) at 37°C, and the clotting time when the blood lost its fluidity was recorded. Red blood cell and platelet adhesion experiments were performed to evaluate the effects and recruitment capabilities of different materials on these cells. Before the test, red blood cells and platelet-rich plasma were separated by centrifugation (1500 rpm, 10 min). Two types of sponges (10×10×2 mm) containing 100 μL of red blood cells and platelets respectively were incubated with pure protein crowns (50 mg) at 37°C for 10 min. The materials were fixed with 2.5% glutaraldehyde (6 h for red blood cells, 12 h for platelets) and dehydrated by a gradient of ethanol (50%, 60%, 70%, 80%, 90%, and 100%) for 6 × 10 min. The surface and cross-section of the sponges and protein crowns were observed using SEM.

[0041] The whole blood coagulation test results visually demonstrate the clotting ability of different materials. The control group failed to clot within 7 minutes, but even the Without P group (without the protein crown) clotting occurred within 5 minutes. Both the P group and the With P group exhibited clotting performance within 3 minutes. Figure 5 A, Figure 5 B). The BCI test also showed the same results. With increasing incubation time, the material exhibited a lower coagulation index, characterizing superior coagulation ability (B). Figure 5 D、 Figure 5 E). The erythrocyte adhesion assay also characterized that the sponge loaded with the protein crown had a stronger ability to recruit erythrocytes than the pure sponge, which would promote coagulation (E). Figure 5 B). Based on the above coagulation-related experiments, it can be seen that the addition of protein corona particles enhances the hemostatic properties of the sponge.

[0042] (6) Biosafety study of hemostatic sponges To evaluate the biocompatibility of the materials, the cytotoxicity of P, Without P, ​​and With P sponges was assessed using human umbilical vein endothelial cells (HUVECs) at 24 and 48 h. CCK8 assays were performed according to the manufacturer's protocol. Furthermore, cell viability was assessed by live / dead cell staining. P, Without P, ​​and With P extracts were added to 96-well plates of HUVEC cells and incubated for 24 h and 48 h, respectively. Live and dead cells were stained with 5 μL propidium iodide and 15 μL calcin, respectively, and incubated at 37°C in the dark for 20 min. Finally, the cells were examined and imaged using a fluorescence microscope (Nikon, Tokyo, Japan).

[0043] After staining for live / dead cells, cell growth morphology was observed under a microscope. Live cells appeared green, and dead cells appeared red. In the presence of WithP sponges, the vast majority of cells survived after 24 h and 48 h of proliferation, with only a very small number of cells dying. Figure 6 A). Compared with the control group, cells cultured in the With P sponge system showed normal proliferation and maintained normal fibroblast morphology without abnormalities. Furthermore, cell viability was assessed using the CCK8 assay. The results showed no significant difference in cell viability among the P, Without P, ​​and With P sponges, all exhibiting good cell viability. Figure 6 (B) Therefore, the With P sponge is considered non-cytotoxic. Live / dead analysis and CCK8 results showed that the With P sponge enabled HUVEC cells to survive, with a survival rate exceeding 95% after 1 day, demonstrating the inherent biocompatibility of all materials.

[0044] (7) Surgical method and animal in vivo hemostasis model verification In vivo hemostatic performance analysis was conducted using rat liver injury and rat skull defect hemorrhage models to evaluate the hemostatic properties of Radial@P sponge. Male SD rats (approximately 250 g) were anesthetized by injection of sodium pentobarbital (40 mg / kg) and fixed on an operating table. In the liver injury model, the fur near the liver was shaved. Subsequently, a 1.5 cm incision was made layer by layer, the liver was removed with forceps and placed on filter paper, and covered with a notched white non-woven fabric. A 1-2 cm incision was made on the liver. Hemostasis was achieved by applying pressure using the sides (edge ​​group) and rectangular sides (center group) of the semi-cylindrical material, respectively, and the hemostatic performance of materials with different pore orientations was compared by time. In the skull defect hemorrhage model, after shaving the fur from the base of the ear to the eye, a disposable surgical drape with a circular incision was laid on top. The epidermis was cut open with a scalpel, and surgical scissors were inserted to separate the scalp from the skull. Sutures were used to pull the scalp apart laterally on both sides of the incision and sutured to the surgical drape to expose the field of vision. The periosteum was gently scraped away with the back of a scalpel to prevent slippage. Finally, a circular defect of known size was drilled into the rat skull using an 8 mm diameter hand drill to induce bleeding. Pre-cut 8 mm diameter Random sponges, Radial hemostatic sponges, and Radial@P hemostatic sponges with a protein crown were applied to different groups of rats, and their hemostatic performance was evaluated by time. Ten rats were randomly divided into two groups of five.

[0045] In the liver hemostasis model, the edge group showed better hemostatic effect due to its positive capillary action, which promoted blood absorption and erythrocyte screening and recruitment. Figure 6 C). In the skull hemostasis model, the loading of a highly coagulable protein crown further enhances the biological hemostatic properties of the radial sponge, building upon the advantages of positive capillary action. Thrombin-induced rapid and efficient hemostasis. The synergistic effect of both physical and biological mechanisms enables the material to achieve hemostasis within 1 minute and 4 seconds. Figure 6 D).

[0046] Hemostasis is a common issue in both clinical and biomedical materials fields. Whether it's uncontrollable continuous bleeding or unexpected intraoperative bleeding, the inability to quickly and effectively stop the bleeding can increase the risk of complications and surgical failure, even leading to death. Current research on hemostatic materials focuses on absorbing and immobilizing blood components, activating coagulation cascade reactions, and forming physical barriers to impede blood flow. This technology uses directional cryo-template casting to prepare a radial silk fibroin sponge substrate, capable of absorbing more than 16 times its own weight in liquid (…). Figure 2B). Its circumferentially contracting gradient channels can trigger the Yong-Laplace effect, rapidly directing blood to the center of the sponge through capillary action. In rat liver hemostasis experiments, the positive capillary action group (edge ​​group) exhibited more than 1.5 times the hemostatic performance compared to the reverse capillary action group (center group). Figure 6 C); simultaneously, the sponge is loaded with highly active thrombin protein coronal particles (CaCO3@CSF / Ca) that have undergone multi-layer modification. 2+ -P), with an average thrombin activity of 1.16 U / mL ( Figure 2 F) can release clotting factors stepwise during blood drainage, activating the coagulation cascade reaction. This design achieves a breakthrough in dynamic synergy between "fluid drainage and coagulation": the central part has a layer spacing of less than 4~5 μm (F). Figure 3 (C) This material can trap red blood cells with an average diameter of 6-9 μm, forming a hematoma structure near the edge to fix the fracture fragment, while plasma components are continuously guided to the central region by capillary action, accelerating thrombin activation. Compared to traditional hemostatic materials, this product combines directional flow guidance, rapid coagulation, and bone repair assistance functions, demonstrating highly efficient hemostatic performance with coagulation within 1 min 4 s in a rat skull defect model. Figure 6 D). The unique biophysical synergistic mechanism of this technology provides a completely new solution for hemostasis of skull defects.

Claims

1. The primary focus is on protecting a silk fibroin sponge with a regularly radially arranged fluid-guiding structure, used for bone hemostasis in scenarios with known bone defect sizes. This sponge is loaded with a highly coagulable protein crown to achieve a synergistic and rapid hemostasis through both physical and biological mechanisms. Among these, The technical solutions to be protected by this patent are not limited to silk fibroin sponges and protein crowns that generate thrombin in situ, but include all hemostatic sponges with radial structures and other hemostatic particles that mimic thrombin and have similar principles.

2. The preparation process of the porous matrix precursor solution of the silk fibroin hemostatic sponge with a regularly radially arranged fluid-conducting structure before freeze-drying is as follows: After obtaining a 3% (w / v) silk fibroin solution by dissolving it in a ternary solution, 0-15% (w / w) glycerol is added, and 0-200 μL of the cross-linking agent ethylene glycol diglycidyl ether (EGDE) is added to every 10 mL of 11% (w / v) silk fibroin protein solution. After mixing at room temperature, 7 μL of tetramethylethylenediamine is added to every 10 mL of the mixed solution to catalyze the reaction, and the reaction is carried out for 10 min.

3. The concentration of the silk fibroin solution is 0-5% (w / v), preferably 3%; the concentration of glycerol is 0-15% (w / w), preferably 5%; the crosslinking agent is not limited to ethylene glycol diglycidyl ether, but includes all alternatives with similar principles that connect hydroxyl groups through epoxy group opening. If ethylene glycol diglycidyl ether is used, its concentration is 0-200 μL per 10 mL of 11% (w / v) silk fibroin solution, preferably 100 μL; the catalyst is not limited to tetramethylethylenediamine, and if used, its concentration is 7 μL per 10 mL of mixed solution.

4. A silk fibroin hemostatic sponge with a regularly radially arranged fluid-conducting structure, the preparation process of which is as follows: A specially made cylindrical mold is prepared. A cylindrical tube is made using rapidly heat-conducting copper (in the embodiments given in this technology, a cylindrical tube with an inner diameter of 3 cm, an outer diameter of 4.6 cm, and a height of 4 cm is made). The bottom is insulated with a 1 cm thick layer of polyvinylidene fluoride (PVDF). Radial freezing is performed using directional cryogenic casting technology. Specifically, liquid nitrogen is poured into a foam box, making the liquid level slightly greater than 1 cm. A mixed solution is poured into the mold, and the mold is immediately placed in liquid nitrogen. Ice crystals are allowed to grow completely from the cylindrical tube wall towards the center. The mold is then placed in a -80°C freezer for at least 15 minutes to fix it. The mold is then freeze-dried in a freeze dryer for 2-3 days. After demolding, a silk fibroin hemostatic sponge with a regularly radially arranged fluid-conducting structure is obtained. Its characteristic is that... The specially designed molds used are not limited to copper and PVDF materials, but include alternatives such as all metals with excellent thermal conductivity for the cylindrical tube and a material with excellent thermal insulation for the bottom. The cryogenic liquid is not limited to liquid nitrogen, but includes all liquids with temperatures ranging from -10 to -200°C. A key detail of this technology is that the insulation material must be thicker than 1 cm, and when pouring the cryogenic liquid, the liquid level should only be slightly higher than the insulation material, not too much. If the height of the cylindrical tube (excluding the bottom) is less than 2 cm, the liquid level must be even lower to prevent excessively rapid freezing and splashing of the cryogenic liquid into the mold, which could affect the molding process.

5. Highly coagulable protein corona (CaCO3@CSF / Ca 2+ -P) and protonated tranexamic acid (TXA-NH3) + The preparation of CaCO3@CSF / Ca was carried out according to previously reported techniques. This technique protects the particle loading step; specifically, CaCO3@CSF / Ca is first loaded with CaCO3. 2+ -P particles and TXA-NH3 + The powders are physically mixed at a molar ratio of 1:

1. A radial sponge is placed in a container containing the mixed powder and gently shaken for 5 minutes. The mixed particles containing a highly coagulating protein corona are then electrostatically adsorbed onto the sponge surface. The characteristic feature is that... The mixing molar ratio is 1:1 to ensure that the two can fully react and ablate upon contact with blood, preventing particles from remaining at the bleeding site.

6. The method of use, characterized in that: Based on the common defect sizes in craniotomy, the hemostatic sponge is pre-cut to a diameter suitable for defects ranging from 3 to 80 mm. Large-sized sponges are made using large-sized molds, while small-sized sponges can be made using small molds or by cutting. Specifically, before the fourth stage of the preparation process—the loading of protein crown particles—the demolded radial sponge is cut into thin slices with a thickness of 1.5 cm to fit the thickness of the human skull, so as not to compress the cranial nerves or brain tissue due to excessive thickness. The radial sponge slices are immersed one by one in liquid nitrogen for 3 seconds, removed for 9 seconds, and immediately cut using a central cutter of different diameters to obtain radial sponges that can adapt to different defect sizes. After loading the mixed particles containing highly coagulating protein crowns, they can be stored for later use. During the procedure, if bleeding occurs at the burr site, a hemostatic sponge can be placed at the bleeding site. As the sponge rapidly absorbs blood and drains fluid, its contraction causes the thrombin particles to trigger a coagulation cascade reaction, resulting in rapid hemostasis. The mixed particles also react with each other and self-dissolve, preventing particle residue or migration to other sites. After hemostasis is achieved, the sponge is removed to proceed to the next step.